On the optimal control of a cascade of hydro-electric power stations - Ribeiro, A. F. (2012)
In this paper we consider a model for a cascade of hydroelectric power stations where some of the stations have reversible turbines. The objective of our work is to optimize the profit of power production satisfying restrictions on the water level in the reservoirs. The problem is considered in the framework of discretetime optimal control and is solved using numerical methods. The optimization uses real data of market prices of electricity, water levels at the reservoirs, and water flows in different types of days.